Medication Risk‐Taking Behavior in Functional Dyspepsia Patients. Issue 1 (January 2015) - Lacy, Brian E; Yu, Jerry; Crowell, Michael D
Abstract : OBJECTIVES: : No medication is approved for the treatment of functional dyspepsia (FD). The risks that patients would be willing to take to cure their FD symptoms are unknown. METHODS: : FD patients (Rome III criteria) were mailed a questionnaire that assessed demographics, medication use, and prior medication adverse events. Scales to measure FD severity, quality of life, anxiety, depression, impulsiveness, and risk‐taking behavior were included. A standard gamble (SG) evaluated willingness to take risks associated with a theoretical FD medication. Data were analyzed using simple descriptive statistics. RESULTS: : One hundred and fourteen responses were analyzed (54.5% response rate). The mean age of the patients was 49.2 years; 84% were women and 96% were white. The mean duration of symptoms was 8.2 years (range 1–38 years). The most bothersome symptom was upper abdominal discomfort (25%), followed by upper abdominal pain (22%) and bloating (15%). Forty percent of respondents rated their FD symptoms as moderate and 31% as mild. Forty‐six percent reported a side effect from a prescription medication used to treat FD. When asked about a hypothetical medication that could cure their FD symptoms, 49% of respondents reported that they would accept a mean 12.7% risk of sudden death for a 99% chance of cure. CONCLUSIONS: : This prospective study suggests that FD patients are surprisingly willing to take significant risks with a hypothetical medication to cure their symptoms. To counsel patients effectively and assist in the development of informed, preference‐based decisions regarding medication therapy, physicians need to elicit and understand FD patients' risk adversity.